The final stages of polarization and monodomain state stability of the Rochelle salt crystals - Romanyuk, M.O.; Romanyuk, M.M. (Condensed Matter Physics, 2002)
Based on the direct domain observations in the Rochelle salt crystals, the final stages of polarization and the dependence of polarized state stability on the electric field strength E and on the electric pulse duration is investigated. The conclusion is made that there exists a high electric field strength, at which small domains are displaced. At higher fields, electrooptical effects are obviously developed and the invisible network of defects is changed. The stability of the polarized state and the degree of polarization are determined by the electric field pulse, the duration τ and the electric strength of which E are connected by equation ln τ ∼ k/E + b . For incomplete polarization, the rate of polarization decay when the pulse is finished is proportional to the deviation of the domains from the initial state of the sample.